Effectiveness of collaborative problem based learning on critical thinking, academic motivation and emotion regulation of secondary school students in kerala - Linisha C K (Research Centre in Education, Farook Training College, 2023)
Background of the Study 21 th century is characterized by technology driven era and technology assisted teaching- learning process. But present education system provides only routine information and content knowledge to the learners. Students develop through this system, without contributing much to their understanding and problem solving capacity. Students learn only what they got from the classroom and content transacted. They do not think how to learn, what to learn and how to integrate the knowledge and how to apply these knowledge in real life. It doesn’t promote any cognitive and affective skills for the learner. Now a days grade points and achievement scores increases but quality of education is deteriorating .In such a situation an innovative instructional strategy is needed for promoting students academic success through meaningful learning like CPBL. Definition of Key Terms Effectiveness Effectiveness refers to the intervention’s ability to do more good than harm for the target population in real-world settings (Schillinger, 2010). In the present study Effectiveness is operationally defined as the extent to which Collaborative Problem Based Learning modules enhance Critical Thinking, Academic Motivation, and Emotion Regulation of adolescent students at the secondary level in terms of different dimensions of Critical Thinking, Academic Motivation and Emotion Regulation. Collaborative Problem Based Learning In the present study Collaborative Problem Based Learning is operationally defined as an instructional strategy used for instruction, here a problem is presented to the student and has to be solved by active collaboration in groups and gathering information from various resources as part of self-regulated learning. Problem Based Learning takes place in a collaborative learning group. Critical Thinking Critical Thinking is the reasonable, reflective thinking that is focused on deciding what to believe or do (Ennis, 1987) In the present study, Critical Thinking is the higher order thinking skill, and the scores obtained through Critical Thinking Test which includes the component of Inference, Recognition of Assumptions, Deduction, Interpretation, and Evaluation of Arguments. Academic Motivation Academic Motivation is a student's desire (as reflected in approach, persistence, and level of interest) regarding academic subjects when the student's competence is judged against a standard of performance or excellence (DiPerna & Elliott, 1999). In the present study, Academic Motivation is the scores obtained through standardized scale of Academic Motivation which includes different components such as Intrinsic motivation, Extrinsic motivation, and Amotivation. Emotion Regulation Emotion regulation involves ‘the extrinsic and intrinsic processes responsible for monitoring, evaluating, and modifying emotional reactions, especially their intensive and temporal features, to accomplish one’s goals’ (Thompson, 1994).In the present study, Emotion Regulation is the scores obtained through standardized scale of Emotion Regulation which includes the component of Identifying, Processing, and Expressing. Secondary School Students In the present study, the term secondary school students are used to denote pupils attending standard VIII in any of the recognized schools of Kerala. Objectives of the study Major Objectives of the Study 1. To develop Collaborative Problem Based Learning modules of 3C3R framework for Secondary School Students. 2. To determine the Effectiveness of the Collaborative Problem-based Learning module on enhancing Critical Thinking, Academic Motivation and Emotion Regulation of secondary school students. Minor Objectives of the Study 1. To assess the Effectiveness of Collaborative Problem Based Learning modules of 3C3R framework on enhancing Critical Thinking and its components, viz., a) Inference b) Recognition of Assumption c) Deduction d) Interpretation e) Evaluation of Arguments 2. To assess the Effectiveness of Collaborative Problem Based Learning modules of 3C3R framework on enhancing Academic Motivation and its components, viz., a) Intrinsic Motivation b) Extrinsic Motivation c) Amotivation 3. To assess the Effectiveness of Collaborative Problem Based Learning modules of 3C3R framework on enhancing Emotion Regulation and its components, viz., Methodology of the study Design Quasi-Experimental pretest posttest nonequivalent group design. Variables Independent Variable Collaborative Problem Based Learning. Dependent Variables Critical Thinking, Academic Motivation and Emotion Regulation. Control Variable Academic achievement is the control variable of the study. The first terminal examination mark of 8 th standard students has taken as the score of academic achievement. Categorical Variable The gender of the student. Sample Two intact class divisions of 89 8th standard students (43 students in experimental group,46 students in control group) of two different schools in Kerala. Instruments used for the study 1 3C3R Model for Collaborative Problem-Based Learning modules (Linisha & Jaseena, 2019). 2 Critical Thinking Test (Francis &Mustafa, 2011). 3 Academic Motivation Scale (Linisha & Jaseena, 2019.) 4 Emotion Regulation Scale (Linisha & Jaseena, 2019 5 Rating Scale on Collaborative Problem-Based Learning (Linisha & Jaseena, 2019) 6 Lesson Transcript on the existing method of teaching (Linisha & Jaseena, 2019) Statistical Techniques used. 1. Test of Significance of the Difference between Means. 2. Analysis of Covariance (ANOVA) 3. Hedges g for Effect Size Major Findings of the study 1. Experimental and control group do not differ significantly in their mean pre-test scores on Critical Thinking and its components inference, recognition of assumptions, deduction , interpretation and evaluation of arguments . 2. There exist a significant difference in mean post-test scores on Critical Thinking and its components inference, recognition of assumption ,deduction, interpretation and evaluation of argument of experimental and control group 3. There exist a significant difference in mean pre test and post test score on Critical Thinking and its components inference, recognition of assumption, deduction, interpretation and evaluation of arguments of experimental group. 4. Collaborative problem based learning has large effect on Critical Thinking and its components inference and recognition of assumption. Collaborative problem based learning has medium effect on deduction, interpretation and evaluation of arguments. 5. Male students in the experimental and control group do not differ significantly in their mean pre test scores on Critical Thinking and it’s components Inference, Recognition of Assumptions, Deduction, Interpretation and Evaluation of arguments. But Male students in experimental and control group have difference in post test scores on Critical Thinking and it’s components Inference, Recognition of Assumptions, Deduction, Interpretation and Evaluation of Arguments. 6. Female students of experimental and control group do not differ significantly in their mean post test scores on component Inference, Deduction and Evaluation of Arguments. But there exists significant difference in mean post test scores of Critical Thinking and it’s components Recognition of Assumption and Interpretation in experimental group.. 7. Experimental and control group do not differ significantly in their mean pretest scores on Academic Motivation and its components intrinsic motivation and extrinsic motivation. Experimental and control groups differ significantly in their mean pretest scores on amotivation. 8. There exist a significant difference in mean post-test scores on Academic Motivation and its components intrinsic motivation extrinsic motivation and amotivation of experimental and control group 9. There exist a significant difference in mean pretest and posttest score of Academic Motivation and its components intrinsic motivation, extrinsic motivation and amotivation of experimental group. 10. Collaborative problem based learning has large effect on Academic Motivation and its components intrinsic motivation and amotivation. But significant and medium effect on component Exrinsic motivation. 11. Male students in experimental and control group shows significant difference in mean post-test scores on Academic Motivation and its components Intrinsic Motivation, Extrinsic Motivation and Amotivation 12. Female students in experimental and control group shows significant difference in mean post-test scores on Academic Motivation and its components Intrinsic Motivation and Amotivation. But there is no significant effect on component Extrinsic motivation.. 13. Experimental and control group do not differ significantly in their mean pre-test scores on Emotion Regulation and its components Identifying and processing. Experimental and control groups differ significantly in their mean pre-test scores on Expressing. 14. There exist a significant difference in mean post-test scores on Emotion Regulation and its components Identifying, processing and expressing of experimental and control group. 15. There exist a significant difference in mean pre test and post test score on Emotion Regulation and its components identifying, processing and expressing of experimental group. 16. Collaborative problem based learning has medium effect on Emotion Regulation and its components processing and expressing. Collaborative problem based learning has small effect on identifying. 17. Male students in experimental and control group shows significant difference in mean post-test scores on Emotion Regulation and its components Processing and Expressing .However There is no significant difference in mean post-test scores on component Identifying. Female students in experimental and control group shows significant difference in mean post-test scores on Emotion Regulation and its components Identifying and Processing and Expressing. Educational Implications of the Study The findings of the study established that Effectiveness of Collaborative Problem Based Learning is effective for enhancing Critical Thinking, Academic Motivation and Emotion Regulation of Secondary School Students in, Kerala which can directly applied in school education. Implication for School Education  CPBL modules are prepared based on 3C3R, which can be administered to improve school education.  School education curriculum can be changed in to interdisciplinary in nature.  Critical Thinking is an essential skill for solving real life problems, so this will help to improve critical thinking.  CPBL provides possibility of self regulated learning in classroom. It will reduce stress and anxiety to the examination, homework and also improves Emotion Regulation in children. By implementing CPBL, the school education can reshape in a better way.  CPBL strengthens Critical Thinking and Academic Motivation which are necessary quality in the academic success and future life. To append effective instructional strategy like CPBL as part curriculum plan. Development of interdisciplinary contents. Recommendations  CPBL Facilitate supportive and democratic learning environment.  3C3R Frame work may be applied in various training program such as Pre service Training.  CPBL enhances Cognitive and affective development of the learner.  Promote Child Centered and Interdisciplinary Curriculum.  Lowering curriculum load.  Critical Thinking and Emotion Regulation are to be considered as a major priority area in school curriculum that will promote Academic Motivation in children.
1. Introduction -- 2. Review of related literature -- 3. Methodology -- 4. Analysis and interpretation -- 5. Summary findings and conclusion -- 6. Recommendations
Thesis (Ph.D)- Research Centre in Education, Farook Training College, 2023
Keywords: Academic Motivation; Emotion Regulation; Secondary School Students